FT- SERS Study of Adriamycin - DNA Intraction - Amanollah Aminzadeh (Iranian Journal of Chemistry & Chemical Engineering, 2003)
FT-SERS (Fourier Transform Surface Enhanced Raman Scattering) of adriamycin and its complex with DNA is reported. It is shown that in agreement with previous Raman studies the interaction of adriamycin  with DNA takes place through an intercalation mechanism. The presence of a new band at 731 cm-1 suggests that ring D of adriamycin is not involved in the intercalation process.